Nonimmune cells contribute to crosstalk between immune cells and inflammatory mediators in the innate response to Trypanosoma cruzi infection - Aoki, Maria del Pilar (2012)
Chagas myocarditis, which is caused by infection with the intracellular parasite Trypanosoma cruzi, remains the major infectious heart disease worldwide. Innate recognition through toll-like receptors (TLRs) on immune cells has not only been revealed to be critical for defense against T. cruzi but has also been involved in triggering the pathology. Subsequent studies revealed that this parasite activates nucleotide-binding oligomerization domain- (NOD-)like receptors and several particular transcription factors in TLR-independent manner. In addition to professional immune cells, T. cruzi infects and resides in different parenchyma cells. The innate receptors in nonimmune target tissues could also have an impact on host response. Thus, the outcome of the myocarditis or the inflamed liver relies on an intricate network of inflammatory mediators and signals given by immune and nonimmune cells. In this paper, we discuss the evidence of innate immunity to the parasite developed by the host, with emphasis on the crosstalk between immune and nonimmune cell responses.